Comparison of the Postoperative Analgesic Effects between Ultrasound-Guided Transmuscular Quadratus Lumborum Block and Thoracic Paravertebral Block in Laparoscopic Partial Nephrectomy Patients: A Randomized, Controlled, and Noninferiority Study. (21st February 2023) - Wang, Jin; Cui, Xulei; Ren, Liying; Li, Xu; Zhang, Yuelun; Xie, Yi; Ji, Zhigang; Huang, Yuguang
Abstract : Background . This prospective, randomized, double-blinded, noninferiority study aimed to compare the effects of analgesia and recovery between transmuscular quadratus lumborum block (TMQLB) and paravertebral block (PVB). Methods . Sixty-eight, American Society of Anesthesiologists level I–III patients, who underwent laparoscopic partial nephrectomy in Peking Union Medical College Hospital were randomly allocated to either TMQLB or PVB group (independent variable) in a 1 : 1 ratio. The TMQLB and PVB groups received corresponding regional anesthesia preoperatively with 0.4 ml/kg of 0.5% ropivacaine and follow-up at postoperative 4, 12, 24, and 48 hours. The participants and outcome assessors were blinded to group allocation. We hypothesized that the primary outcome, postoperative 48-hour cumulative morphine consumption, in the TMQLB group was not more than 50% of that in the PVB group. Secondary outcomes including pain numerical rating scales (NRS) and postoperative recovery data were dependent variables. Results . Thirty patients in each group completed the study. The postoperative 48-hour cumulative morphine consumption was 10.60 ± 5.28 mg in the TMQLB group and 6.40 ± 3.40 mg in the PVB group. The ratio (TMQLB versus PVB) of postoperative 48-hour morphine consumption was 1.29 (95% CI: 1.13–1.48), indicating a noninferior analgesic effect of TMQLB to PVB. The sensory block range was wider in the TMQLB group than in the PVB group (difference 2 dermatomes, 95% CI 1 to 4 dermatomes, P = 0.004 ). The intraoperative analgesic dose was higher in the TMQLB group than in the PVB group (difference 32 µ g, 95% CI: 3–62 µ g, P = 0.03 ). The postoperative pain NRS at rest and on movement, incidences of side effects, anesthesia-related satisfaction, and quality of recovery scores were similar between the two groups (all P > 0.05 ). Conclusions . The postoperative 48-hour analgesic effect of TMQLB was noninferior to that of PVB in laparoscopic partial nephrectomy. This trial is registered with NCT03975296